2010
DOI: 10.1002/hipo.20705
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal NMDA receptor subunits differentially regulate fear memory formation and neuronal signal propagation

Abstract: Activation of NMDA receptors (NMDAR) in the hippocampus is essential for the formation of contextual and trace memory. However, the role of individual NMDAR subunits in the molecular mechanisms contributing to these memory processes is not known. Here we demonstrate, using intrahippocampal injection of subunit-selective compounds, that the NR2A-preferring antagonist impaired contextual and trace fear conditioning as well as learning-induced increase of the nuclear protein c-Fos. The NR2B-specific antagonist, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
73
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 56 publications
6
73
1
Order By: Relevance
“…These data obtained in C57BL/6 mice are in agreement with our previous work performed on Swiss mice (Benchenane et al, 2007), showing then the phenotypic consistency of the mechanism across these mouse strains. In addition, our present data reveal that, although NMDARs are involved in emotional memory (Levenson et al, 2002;Bardgett et al, 2003;Gao et al, 2010), the influence of tPA on this process cannot be explained by its ability to promote NMDAR-dependent signaling. It is well admitted that the establishment of emotional memory also involves BDNF (Liu et al, 2004b).…”
Section: Discussioncontrasting
confidence: 55%
“…These data obtained in C57BL/6 mice are in agreement with our previous work performed on Swiss mice (Benchenane et al, 2007), showing then the phenotypic consistency of the mechanism across these mouse strains. In addition, our present data reveal that, although NMDARs are involved in emotional memory (Levenson et al, 2002;Bardgett et al, 2003;Gao et al, 2010), the influence of tPA on this process cannot be explained by its ability to promote NMDAR-dependent signaling. It is well admitted that the establishment of emotional memory also involves BDNF (Liu et al, 2004b).…”
Section: Discussioncontrasting
confidence: 55%
“…However, our recent study, along with others, demonstrated that activation of ex-NMDAR failed to shut off prosurvival signaling (17,50) and did not trigger cell death (17,51). It is interesting to note that certain types of neurons (such as retinal ganglion cells) only express ex-NMDAR and are resistant to glutamate-induced excitotoxicity (52).…”
Section: Discussionmentioning
confidence: 77%
“…Although we did not perform direct comparisons between the DH and RSC (because the experiments were performed separately, at different times, and in different behavioral rooms, resulting in different freezing levels in vehicle controls), the observed effects point toward a model of muscarinic contribution to retrieval that is multifaceted and non-uniform across brain regions. Unlike other neurotransmitter receptors such as NMDAR (Gao et al 2010), AMPA receptors (Schiapparelli et al 2006;Bannerman 2009), adrenergic receptors (Gibbs and Summers 2002;Galeotti et al 2004), and dopamine receptors (Sarinana et al 2014;Sarinana and Tonegawa 2016) for which the roles of specific receptor subunits or subtypes are clearly discriminable in various memory processes, it seems that activation of several mAChR subtypes may be necessary to maximally effect one process. This model is consistent with findings using electrophysiological approaches, which demonstrate that cortical M 1 , M 2 , and M 4 together exert a "triad of effects" (M 1 increases neuronal firing rates, M 2 mediates a decrease in cellular inhibition, and M 4 depresses excitatory transmission), which may underlie attention and learning (Gigout et al 2012).…”
Section: Discussionmentioning
confidence: 99%